2014
DOI: 10.1002/chem.201404372
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Bisethynyl[60]fulleropyrrolidine Scaffolds for Mimicking Artificial Light‐Harvesting Photoreaction Centers

Abstract: Fullerene-based tetrads, triads, and dyads are presented in which [60]fulleropyrrolidine synthons are linked to an oligo(p-phenyleneethynylene) antenna at the nitrogen atom and to electron-donor phenothiazine (PTZ) and/or ferrocene (Fc) moieties at the α carbon of the pyrrolidine cycle through an acetylene spacer. Cyclic voltammetry and UV/ Vis absorption spectra evidence negligible ground-state electronic interactions among the subunits. By contrast, strong excited-state interactions are detected upon selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Steady-state emission spectra recorded for (10-hexyl-3formyl)phenothiazine and (10-triethylene monomethyl ether-3formyl)phenothiazine revealed a broad emission at 520 nm while this emission for 10-(4-formylphenyl)phenothiazine was at 450 nm in DCB (see Figure S19 in the Supporting Information). However, for the dyads, no emission from either phenothiazine (400−650 nm range) 32 or fulleropyrrolidine (675−800 nm range) 30 entities was observed, suggesting the occurrence of excited-state events in these dyads.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Steady-state emission spectra recorded for (10-hexyl-3formyl)phenothiazine and (10-triethylene monomethyl ether-3formyl)phenothiazine revealed a broad emission at 520 nm while this emission for 10-(4-formylphenyl)phenothiazine was at 450 nm in DCB (see Figure S19 in the Supporting Information). However, for the dyads, no emission from either phenothiazine (400−650 nm range) 32 or fulleropyrrolidine (675−800 nm range) 30 entities was observed, suggesting the occurrence of excited-state events in these dyads.…”
Section: Resultsmentioning
confidence: 93%
“…Incidentally, phenothiazine (PTZ), which is an electroactive heterocyclic compound with electron-rich S and N atoms, have recently attracted considerable interest as electron donors and sensitizers in dye-sensitized solar cells (DSSCs) . Consequently, donor–acceptor dyads comprised of phenothiazine and fulleropyrrolidine (PTZ-C 60 ) have been investigated for their ability to undergo photochemical charge separation and applications in organic solar cells. , It has been suggested that the donor–acceptor dyads provide sufficient HOMO–HOMO and LUMO–LUMO offsets of the donor and acceptor entities to help exceed the Coulombic attraction of the hole–electron pair, which is necessary to overcome the exciton binding energy to avoid the back charge transfer. , …”
Section: Introductionmentioning
confidence: 99%
“…Thus, ferrocene‐extended Prototype II compounds could not be synthesized. In addition, recent studies suggest that ferrocene may hamper energy and electron transfer in multicomponent scaffolds 34…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ferrocene-extendedP rototypeIIc ompounds could not be synthesized.I naddition, recent studies suggest that ferrocene may hamper energy and electron transfer in multicomponents caffolds. [34] Compounds 2 and 4 could be used as lead structures for rigid derivatives and derivatives which carry higherg eneration dendrons for mediation of water solubility.…”
Section: Synthesis Of Prototype II Compoundsmentioning
confidence: 99%